Study protocol for a stepped-wedge implementation study investigating the intersectoral collaboration of implementing the TREAT INTERACT intervention for primary school teachers and the mhGAP for health care workers for child mental health promotion in Uganda - Ane-Marthe Solheim Skar; Ingunn Marie S. Engebretsen; Nora Braathu; Harriet Aber; Harald Bækkelund; Melf-Jakob Kühl; Marjorie Mukisa; Joyce Sserunjogi Nalugya; Norbert Skokauskas; Vilde Skylstad; Tore Wentzel-Larsen; TREAT research consortium; et al. (Trials)
Abstract Background Mental and neuropsychological disorders make up approximately 14% of the total health burden globally, with 80% of the affected living in low- and middle-income countries (LMICs) of whom 90% cannot access mental health services. The main objective of the TREAT INTERACT study is to adapt, implement, and evaluate the impact of a novel, intersectoral approach to prevent, identify, refer, and treat mental health problems in children through a user centred task-sharing implementation of the TREAT INTERACT intervention, inspired by the World Health Organization (WHO) Mental Health Gap Action Programme Intervention Guide (mhGAP-IG) for primary school staff in Mbale, Uganda. Health care personell will be trained in the mhGAP-IG. Methods This is a pragmatic mixed-methods hybrid Type II implementation-effectiveness study utilizing a co-design approach. The main study utilize a stepped-wedged trial design with six starting sequences, randomizing three schools to the intervention at each interval, while the remaining act as “controls”. Other designs include a nested prospective cohort study, case control studies, cross-sectional studies, and qualitative research. Main participants’ outcomes include teachers’ mental health literacy, stigma, and violence towards the school children. Implementation outcomes include detection, reach, sustainability, and service delivery. Child and caregiver outcomes include mental health, mental health literacy, and help-seeking behaviour. Discussion Based on the results, we will develop sustainable and scalable implementation advice on mental health promotion and draft implementation guidelines in line with current WHO guidelines. This project will generate new knowledge on the structure, organization, delivery, and costs of mental health services in a LMIC setting, as well as new knowledge on the implementation and delivery of new health services. Trial registration ClinicalTrials, NCT06275672, 28.12.2023, retrospectively registered.